P28 | EXPLORING THE POTENTIAL LINK BETWEEN MITOCHONDRIAL DYSFUNCTION AND MITO-EVS IN PANCREATIC DUCTAL ADENOCARCINOMA (PDAC) (European Journal of Histochemistry)
The trafficking of mitochondrial cargoes in the extracellular space has been associated with tumor survival and chemoresistance in several human cancers1. Furthermore, a significant enrichment of mitochondria-derived extracellular vesicles (mito-EVs) carrying specific mutations in (mt)DNA has been recently reported in the serum of patients with pancreatic ductal adenocarcinoma (PDAC)2. Since we had previously observed exocytosis of fragmented mitochondria by a specific PDAC aggressive histotype3, we sought to correlate the metabolic reprogramming of PDAC cells, involving mitochondria dysfunction, with the intercellular shuttle of mitochondrial cargoes mediated by EVs. First, we evaluated via cytofluorimetric analysis the presence of the translocase of outer mitochondrial membrane, (TOMM) 20 marker, in cell-conditioned media derived from 2D-PDAC in vitro cell cultures, finding that, compared to non-malignant cells (HPDE), cancer cells (PANC-1, BXPC3) release a higher amount of EVs of mitochondrial origin (TOMM20+). RT- PCR performed on EVs, isolated by ultracentrifugation, confirmed that tumor-derived EVs also contained more mtDNA than those derived from control cells. Interestingly, PANC-1 and BXPC3 exhibited a different potential in secreting mitochondrial cargoes, that might be function of their metabolic phenotypes and KRAS-signatures. Thus, to better explore this possible link, we went to assess the quantity and the quality of EVs release by patient-derived organoids (PDOs)4. In this way, we would add strong evidence to support mito-EVs as a new parameter for stratifying PDAC sub-populations.